Prevalence and characteristics of transesophageal echocardiography-related esophageal mucosal injury in patients with atrial fibrillation who underwent pulmonary vein isolation. (1st March 2022) - Omuro, Ayumi; Wada, Yasuaki; Yoshiga, Yasuhiro; Okuda, Shinichi; Okamoto, Takeshi; Fukuda, Masakazu; Omuro, Takuya; Maeda, Takako; Kinoshita, Natsu; Okamura, Takayuki; Nishikawa, Jun; Takami, Taro; et al.
Abstract: Background: Transesophageal echocardiography (TEE) is the gold standard for detecting thrombi in the left atrium (LA) and left atrial appendage (LAA) prior to pulmonary vein isolation (PVI) for the treatment of atrial fibrillation (AF). Although TEE has a good safety profile, it was recently reported that TEE preceding PVI can cause esophageal mucosal injuries (EMIs). The exact mechanism remains to be elucidated. In the present study, we investigated the incidence and risk factors of TEE-related EMI (TEE-EMI) among patients who underwent PVI for AF. Methods and results: This study included 262 consecutive patients who underwent PVI with preoperative TEE using a 3D TEE probe and postoperative esophagogastroduodenoscopy. TEE-EMIs were observed in 16 (6.1%) patients (18 lesions), whereas PVI-related EMIs were found in 5 (1.9%) patients (8 lesions). All TEE-EMIs were observed in the upper or middle esophagus and occurred more frequently in the right region of the upper esophagus and the left anterior region of the middle esophagus; only one patient experienced mild chest discomfort. In the multivariate analysis, advanced age was an independent risk factor for TEE-EMIs (odds ratio 1.08, 95% confidence interval 1.01–1.16; P = 0.0274). Conclusions: The incidence of TEE-EMIs with 3D TEE probes was relatively high in the upper or middle esophagus, anatomically close to the LA, among patients who underwent PVI. Advanced age could pose a significant risk. These findings may warrant consideration of other methods to rule out LA/LAA thrombi, especially in elderly patients. Graphical abstract: Unlabelled Image Highlights: TEE-related esophageal mucosal injury noted in 6.1% of pulmonary vein isolations. Advanced age was the only risk factor for TEE-related esophageal mucosal injury. Indications for TEE before pulmonary vein isolation should be carefully considered.